A short history of Irish traditional music - Ó hAllmhuráin, Gearóid (Short histories, 2017)
The history of Irish traditional music, song and dance from the mythological harp of the Dagda to Riverdance, Lord of the Dance and beyond. Featuring the tradition's finest musicians and international names